Answer:
m = (-13)/20
Explanation:
Solve for m:
6 (3 m + 1) = -2 m - 8 - 4 + 5
Grouping like terms, -2 m - 8 - 4 + 5 = -2 m + (-8 + 5 - 4):
6 (3 m + 1) = -2 m + (-8 + 5 - 4)
-8 + 5 - 4 = -7:
6 (3 m + 1) = -7 - 2 m
Expand out terms of the left hand side:
18 m + 6 = -2 m - 7
Add 2 m to both sides:
18 m + 2 m + 6 = (2 m - 2 m) - 7
2 m - 2 m = 0:
18 m + 2 m + 6 = -7
18 m + 2 m = 20 m:
20 m + 6 = -7
Subtract 6 from both sides:
20 m + (6 - 6) = -6 - 7
6 - 6 = 0:
20 m = -6 - 7
-6 - 7 = -13:
20 m = -13
Divide both sides of 20 m = -13 by 20:
(20 m)/20 = (-13)/20
20/20 = 1:
Answer: m = (-13)/20